Cavity quantum electrodynamics : the strange theory of light in a box - Dutra, S. M. (Sergio M.) (Wiley series in lasers and applications., 2005)
What happens to light when it is trapped in a box?Cavity Quantum Electrodynamics addresses a fascinating question in physics: what happens to light, and in particular to its interaction with matter, when it is trapped inside a box? With the aid of a model-building approach, readers discover the answer to this question and come to appreciate its important applications in computing, cryptography, quantum teleportation, and opto-electronics.